Patient-reported outcome measures (PROMs) in helthcare chaplaincy: What, why and how (Tidsskrift for Praktisk Teologi, 2019)
Outcome research is becoming increasingly important in healthcare chaplaincy, to improve the quality of chaplaincy care and to justify the need for healthcare chaplaincy services. Patient-reported outcome measures (PROMs) are instruments enabling the assessment of healthcare chaplaincy outcomes. In this paper, I discuss how PROMs might be implemented in healthcare chaplaincy. PROMs can be used for patient monitoring, quality improvement and external transparency. PROMs can reflect any dimension of patient health and functioning, but they must be sensitive to change and relevant to the chaplaincy care context that is being evaluated. The choice of PROsassessed reflects the vision on the profession and its responsibility. Reduction of the profession to that which can be measured with PROMs should be avoided. Thus, the selection and implementation of PROMs in healthcare chaplaincy requires careful considerations, which can be supported by use of the PROM cycle illustrated in this paper.